Public service announcement during COVID-19 pandemic in Malaysia: analysis of themes / Nalini Arumugam ... [et al.] - Arumugam, Nalini; Latiff Azmi, Mohd Nazri; Shanthi, Alice; -, Puwarno; Supramaniam, Kaarthiyainy (Universiti Teknologi MARA Cawangan Sarawak, 2024)
Public Service Announcements (PSA) is an important source of information for the public especially during a crisis such as the recent COVID-19 pandemic. Governments utilise PSA to implement strategies that could reach the masses in the quickest and mostefficient means. During the global crisis, the Malaysian government faced an unprecedented need to reach the populace with its contingency plans. In retrospect, it is important to study the PSA made during the health crisis and to identify the official sources through which health information was conveyed to the public. Therefore, a qualitative approach was adopted whereby COVID-19 related PSA published between 1-31 March 2022 were generated from three online Malaysian newspapers: Malay Mail, The Star, and New Straits Times. Keywords “COVID-19” and “Public Service Announcement” were used to mine the digital news portal archives. Analysis of categories that emerged were: “endemic phase”, “recovery”, and “international” which made up dominant themes. Also, the Health Minister made the highest number of COVID-19 PSA whereas press conferences was the most common platform for dissemination of government PSA. However, the issue of border reopening was conveyed via social media. It is important to understand the trends of PSA and sources in order to compete with the proliferation of information on social media. An efficient PSA could be a powerful source that satiate public hunger for information during a crisis.